Effectiveness of Motion Graphic-Based Narrative Therapy With a Cognitive-Behavioral Approach in Reducing Fluoride Varnish Therapy Anxiety for Six-Year-Old Children - SHABANI, SEVİL MOMENİ; Darabi, Fatemeh; Azimi, Ahad; Shabani, Masoud (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Fluoride varnish therapy (FVT) is a dental caries preventive service that its effectiveness has been well documented. A lot of children, especially the five-year-old and six-year-old ones, are suffering with anxiety during this service and do not readily allow it. The present study aimed to cast light on the effect of motion graphic-based narrative story with a cognitive-behavioral approach in reducing FVT anxiety among six-year-old children. MATERIALS AND METHODS:This study was an intervention trial type that was conducted in Ardabil city and among school students. Five children suffering from FVT anxiety were randomly selected for the intervention. First, Venham and Gaulin-Kremer's anxiety scale was completed for them. The motion graphic-based narrative therapy was implemented for six weeks. Session 1 was assigned to filling the questionnaire and collecting data. The motion graphic-based narrative therapy started from the second session. The anxiety scale was filled for the children every ten days for a total of four times. The results were analyzed by Blanchard and Schwarz's progress formula and control charts. The intervention sessions included gathering information, watching motion graphics, relaxation skills, watching the process of performing fluoride varnish therapy, teaching the advantages of fluoride varnish therapy, and in the last session performing fluoride varnish therapy with the technique of attention diversion while watching motion graphics. RESULTS: The motion graphic-based narrative therapy by the cognitive-behavioral approach proved effective in reducing anxiety. At the end of the intervention sessions, the level of anxiety decreased from 8 to 2.2 and the statistical control chart of the process shows that the intervention process is stable and the stability in order to reduce anxiety and the results are within the control limits. CONCLUSION: The results show that motion graphic-based narrative therapy can be a psychotherapy method for reducing the symptoms of dental anxiety among children.
Keywords: Art Therapies; Cognitive Behaviour Therapies; Dental Anxieties; Narrative Therapies